The Definition of the Optimal Energy-Efficient form of the Building - Sergeychuk, Oleg; Martynov, Viacheslav; Usenko, Dmytro (International Journal of Engineering and Technology, 2018)
We consider the problem of finding a geometrical form of a body in a thermal radiation field, for which the thermal balance between the body and the surrounding air is minimal. The case of a point source of heat is investigated. To consider an analogous problem for buildings, one must know the value of incoming thermal energy to a unit square in relation to its orientation. We develop an application package in MATLAB that represents this relation in table form and takes into consideration the direct, diffuse, ground-reflected solar radiation and the thermal radiation of atmosphere.Â Â